Ciliate Communities Respond via Their Traits to a Wastewater Treatment Plant With a Combined UASB–Activated Sludge System - Moreira, Yasmine Costa; Cardoso, Simone Jaqueline; Siqueira-Castro, Isabel Cristina Vidal; Araújo Greinert-Goulart, Juliane; Bueno Franco, Regina Maura; Graco-Roza, Caio; Dias, Roberto Júnio Pedroso (Frontiers in Environmental Science, 2022)
Assessing functional diversity of communities is an efficient method to link community composition to ecosystem quality. Still, studies using functional traits of microeukaryote ciliate communities in biological wastewater treatment plants are lacking. The present work explores the functional diversity of the ciliate protist community in a wastewater treatment plant (WWTP) operating with a combined UASB-activated sludge system, and specifically to: (1) investigate the taxonomic and functional composition of the ciliate communities over time; (2) compare taxonomic and functional diversity indices with regard to its applicability in WWPS; (3) assess the relationship between the ciliate community’s functional composition and the WWTPs temporal conditions; and (4) investigate the potential use of functional diversity as an indicator of WWTP efficiency. Totally, we recorded 21 ciliate species throughout 37 samplings. The number of species was low compared to other plants. Bacterivorous and flake-forming species were the main functional strategies found in the samples. The correlation between taxonomic and functional richness was significant, indicating a functionally redundant community. There was a correlation between the Simpson and Rao's quadratic entropy indexes suggesting that loss of taxonomic diversity leads to a loss of functional diversity. The homogeneity of the measured physical and chemical data led to functional homogenization and redundancy (homogenous CWM) of the ciliate community. The functional diversity is positively correlated with parameters of removal efficiency, indicating a promising application in WWTPs. Future studies will broaden knowledge on functional diversity in biological wastewater treatment systems, this being a first step with the unprecedented application of this methodology in artificial ecosystems.